2023
DOI: 10.1186/s13071-023-05971-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis challenges the presence of Ixodes inopinatus in Central Europe: development of a multiplex PCR to distinguish I. inopinatus from I. ricinus

Kristyna Hrazdilova,
Ondrej Danek,
Alena Hrbatova
et al.

Abstract: Background Ixodes ricinus is an important vector of several pathogens, primarily in Europe. Recently, Ixodes inopinatus was described from Spain, Portugal, and North Africa and then reported from several European countries. In this study, a multiplex polymerase chain reaction (PCR) was developed to distinguish I. ricinus from I. inopinatus and used in the surveillance of I. inopinatus in Algeria (ALG) and three regions in the Czech Republic (CZ). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 54 publications
1
17
0
1
Order By: Relevance
“…Seit einigen Jahren scheint I. inopinatus auch in Süddeutschland und Österreich stabile Populationen zu bilden [12]. Aktuelle genetische Analysen zeigen, dass eine Differenzierung von I. inopinatus und I. ricinus herausfordernd ist und es auch zu einer Hybridisierung der beiden Arten kommen kann, sodass die Ausbreitung in Mitteleuropa nicht vollständig geklärt ist [13,14]. Auch das Vektorpotenzial von I. inopinatus ist noch nicht vollständig geklärt.…”
Section: Zeckenvektoren Und üBertragene Erkrankungenunclassified
“…Seit einigen Jahren scheint I. inopinatus auch in Süddeutschland und Österreich stabile Populationen zu bilden [12]. Aktuelle genetische Analysen zeigen, dass eine Differenzierung von I. inopinatus und I. ricinus herausfordernd ist und es auch zu einer Hybridisierung der beiden Arten kommen kann, sodass die Ausbreitung in Mitteleuropa nicht vollständig geklärt ist [13,14]. Auch das Vektorpotenzial von I. inopinatus ist noch nicht vollständig geklärt.…”
Section: Zeckenvektoren Und üBertragene Erkrankungenunclassified
“…Furthermore, while 16S rDNA is the genetic marker of choice for delineation of other species of the genus Ixodes , recent studies have shown that it is not the appropriate gene target for identifying I. inopinatus [ 12 – 15 ]. Different genetic markers such as the nuclear gene for tick receptor OspA ( TROSPA ), defensin, internal transcribed spacer 2 ( ITS2 ), and mitochondrial cytochrome c oxidase I ( COI ) provided more robust results when compared with tick morphology and 16S rDNA [ 2 , 14 ]. In our previous study, a combination of nuclear and mitochondrial markers was used to assess the differences between I. inopinatus from Algeria and I. ricinus from the Czech Republic, with several specimens showing signs of hybridization between these two species [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different genetic markers such as the nuclear gene for tick receptor OspA ( TROSPA ), defensin, internal transcribed spacer 2 ( ITS2 ), and mitochondrial cytochrome c oxidase I ( COI ) provided more robust results when compared with tick morphology and 16S rDNA [ 2 , 14 ]. In our previous study, a combination of nuclear and mitochondrial markers was used to assess the differences between I. inopinatus from Algeria and I. ricinus from the Czech Republic, with several specimens showing signs of hybridization between these two species [ 14 ]. This study, together with a recent study from Germany, questioned all observations of I. inopinatus outside the Mediterranean Basin based solely on morphology and/or 16S rDNA [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations